Cinzas de caldeira: revisão, caracterização e oportunidades de aproveitamento - Resende, Rafaela da Silva (2025)
The increasing generation of ashes derived from biomass combustion presents both environmental and industrial challenges, requiring strategies for their management and reuse. This study investigated their physicochemical characteristics, sources, and potential applications to promote sustainable alternatives. A literature review was conducted on the influence of combustion technologies on ash composition and its environmental implications. Additionally, a bibliometric analysis was performed to map the progress of scientific production in the field, identifying trends, leading researchers, and prominent journals. The systematic review revealed that most studies focus on the use of fly ash in construction materials, while other possibilities, such as agricultural applications and industrial processes, remain less explored. Simultaneously, the experimental characterization of different types of biomass ashes enabled the assessment of their physical and chemical properties, distinguishing between fly ash and bottom ash. The results showed significant variability in the analyzed parameters, with fly ash exhibiting lower density (435.9 kg/m³) and moisture content (6%, wet basis), while bottom ash had a higher residual carbon content (41.23%), suggesting incomplete combustion. The chemical composition revealed significant concentrations of silica, phosphorus, and potassium, highlighting their potential for agricultural and industrial applications, although the presence of heavy metals (Mn and Zn) may pose environmental risks. The bibliometric analysis indicated significant growth in research on ashes in recent years, with a higher concentration of studies focused on engineering and materials science, while topics such as environmental impact, economic feasibility, and regulation still require further exploration. Moreover, most experiments are conducted on a laboratory scale, without considering operational challenges for large-scale implementation. In conclusion, despite advancements in knowledge about biomass ashes, gaps remain that need to be addressed to ensure their safe and efficient use. Investments in research focused on standardization, life cycle analysis, and environmental impacts are essential to expand reuse possibilities and mitigate the damages caused by improper disposal.